Flame-made TiO2(B). (October 2018) - Riad, Keroles B.; Wood-Adams, Paula M.; Wegner, Karsten
Graphical abstract: Highlights: Flame-made titania can contain up to 27% TiO2 (B). TiO2 (B) is present due to quenching. The fraction of TiO2 (B) depends on residence time at high temperature. Flame-made titania containing TiO2 (B) photocure epoxy more efficiently than P25. Abstract: Titania nanoparticles containing both monoclinic (TiO2 (B) – a promising battery material and catalyst) and anatase crystal phases are synthesized with a low-cost, scalable flame spray pyrolysis (FSP) process, as confirmed by X-ray diffraction, transmission electron microscopy and Raman spectroscopy. The latter reveals TiO2 (B) contents of up to 27% in the crystalline phase fraction. The amount of TiO2 (B) increases as the time for nanoparticle growth in the flame decreases through quenching with ambient air. It can be controlled by varying the flow rates of precursor solution and dispersion oxygen into the flame. The FSP-made titania outperforms commercial titania P25 in the photocuring of epoxy, indicating its potential as a photocatalyst.